There Is No Role for Damage Control Orthopedics Within the Golden Hour. Issue 1 (23rd January 2021) - Dunn, John C; Elster, Eric A; Blair, James A; Remick, Kyle N; Potter, Benjamin K; Nesti, Leon J
ABSTRACT: Introduction: Trauma systems within the United States have adapted the "golden hour" principle to guide prehospital planning with the goal to deliver the injured to the trauma facility in under 60 minutes. In an effort to reduce preventable prehospital death, in 2009, Secretary of Defense Robert M. Gates mandated that prehospital transport of injured combat casualties must be less than 60 minutes. The U.S. Military has implemented a 60-minute timeline for the transport of battlefield causalities to medical teams to include Forward Surgical Teams and Forward Resuscitative Surgical Teams. The inclusion of orthopedic surgeons on Forward Surgical Teams has been extrapolated from the concept of damage control orthopedics (DCO). However, it is not clear if orthopedic surgeons have yielded a demonstrable benefit in morbidity or mortality reduction. The purpose of this article is to investigate the function of orthopedic surgeons during the military "golden hour." Materials and Methods: The English literature was reviewed for evidence supporting the use of orthopedic surgeons within the golden hour. Literature was reviewed in light of the 2009 golden hour mandate by Secretary Gates as well as those papers which highlighted the utility of DCO within the golden hour. Results: Evidence for orthopedic surgery within the "golden hour" or in the current conflicts when the United States enjoys air superiority was not identified. Conclusions: Within the military context, DCO, specifically pertaining to fracture fixation, should not be considered an element of golden hour planning and thus orthopedic surgeons are best utilized at more centralized Role 3 facility locations. The focus within the first hour after injury on the battlefield should be maintained on rapid and effective prehospital care combined with timely evacuation, as these are the most critical factors to reducing mortality.